Being a woman - A possible metaphor? In: Semiotic analysis of the representative function of discursive reality - Souza , Mônica Maria Martins de (Seven Editora, 2023)
The (re)representative function of discursive reality analyzes the path of construction of the girl-woman's destiny as a possible metaphor. Step by step, it reveals how a mother seeks psychological help for her daughter and through it reveals herself. It deals with the restlessness arising from a real difficulty of a mother who is distressed by her daughter who repeats the second year of primary school, but this is just the driving/pain fact that launches her on a journey to the past and to her imagination, A understanding of the human ties specifically of the girl and her representations thought up by the mother in the search for self-understanding through the biases of what is said and what is not said. It deals with an inverted demand in which the mother speaks through the daughter. She reflects on fragments of her origin and her story that appears little by little and incomplete. A reality composed of beliefs, fantasies, anguish, dreams and hopes of happiness that so torment a mother who begs to understand herself as a person and subject of her existence based on what she imagines to be her son's castration. DOI:https://doi.org/10.56238/interdiinovationscrese-016